2020
DOI: 10.3847/1538-4357/ab908d
|View full text |Cite
|
Sign up to set email alerts
|

Fitting the Nonlinear Matter Bispectrum by the Halofit Approach

Abstract: We provide a new fitting formula of the matter bispectrum in the nonlinear regime calibrated by high-resolution cosmological N-body simulations of 41 cold dark matter (wCDM, w =  constant) models around the Planck 2015 best-fit parameters. As the parameterization in our fitting function is similar to that in Halofit, our fitting is named BiHalofit. The simulation volume is sufficiently large ( ) to cover almost all measurable triangle bispectrum c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(89 citation statements)
references
References 132 publications
6
82
1
Order By: Relevance
“…These expressions are valid in the linear regime, where l 1 ; l 2 ; l 3 < 100 (see e.g., [27]). In order to be able to accurately capture the behavior of the bispectrum beyond this range, we must obtain fitting formulas from N-body simulations [28][29][30]. In this work, we use the fitting formula of [28], to allow consistent comparison with the results of [11].…”
Section: F the Convergence Bispectrummentioning
confidence: 99%
“…These expressions are valid in the linear regime, where l 1 ; l 2 ; l 3 < 100 (see e.g., [27]). In order to be able to accurately capture the behavior of the bispectrum beyond this range, we must obtain fitting formulas from N-body simulations [28][29][30]. In this work, we use the fitting formula of [28], to allow consistent comparison with the results of [11].…”
Section: F the Convergence Bispectrummentioning
confidence: 99%
“…In this paper, we have examined the validity of the reduced shear approximation when applying k-cut cosmic shear to Stage IV cosmic shear experiments, and a hypothetical kinematic lensing survey. We first compared the reduced shear correction calculated using two different models for the matter bispectrum: the fitting formulas of [31], and the BIHALOFIT model [33]. Despite the differences between the two approaches, we found that their resulting reduced shear corrections were not significantly different, and that accordingly the reduced shear correction was robust to the choice of bispectrum model.…”
Section: Discussionmentioning
confidence: 98%
“…Cosmological parameter biases predicted if the reduced shear correction is neglected for two different matter bispectrum models. The SC model uses the fitting formulas of [31], while BH is the BIHALOFIT model [33]. The difference between the two approaches is also stated, and is not significant.…”
Section: B K-cut Cosmic Shear and Reduced Shear For Stage IV Surveysmentioning
confidence: 94%
See 1 more Smart Citation
“…The matter bispectrum required by Eq. ( 30) is computed via the BIHALOFIT model [35] and package [36]. In order to calculate the IA contributions at both the two-point and three-point levels, we use the following values for the NLA model: A IA ¼ 1.72 and C IA ¼ 0.0134 [14].…”
Section: Methodsmentioning
confidence: 99%